Thermal Structural Coupling Analysis of Gradient Coil Casting, Curing and Demolding Method - Xiaotao ZHANG; Zhanping ZHENG; Yicheng LI (Zhongguo yiliao qixie zazhi)
The casting and curing of gradient coils in the production process is a relatively complex process. The chemical process similar to the black box model requires confirmation of the impact of each step of input on the output results, while the curing temperature and molding method affect the roundness and deformation of the gradient coils. The analysis of the curing temperature and demolding method of gradient coils has important practical significance for the formation and micro deformation of gradient coils. This article uses ANSYS finite element simulation software to analyze the thermal structural coupling and the specific performance of actual products. It has been found that the product quality is more stable under the heat conduction mode, and the roundness of the mold is better when placed vertically and waiting for temperature cooling before being demolding than when placed horizontally.